(untitled) (Revista Venezolana de Salud Pública, 2021)
To analyze the effect of the COVID-19 pandemic on the physical activity and consumption of junk food in the youth of Nayarit. The study was descriptive and observational and was conducted between February and August 2020. A total of 1004 young people (16 and 24 years) from the municipalities of Tepic (Tpc, 407), San Pedro Lagunilla (SnPdLg, 186), San Blas (SnBl, 211) and El Nayar (Nay, 200) participated voluntarily. Physical activity (PA) was measured using the IPAQ-C with a frequency scale (0,25,50,75,100%). The frequency of junk food (JF) consumption was assessed following Thompson’s protocol. JF and BP were proposed to be reduced during four weeks. Anthropometric assessment was measured using standard methods. Youth preferred to sit and watch something on the television, computer or cell phone. The consumption of potato chips, cookies, soft drinks and beer increased in all municipalities. Youth in all four municipalities reduced consumption of pizza, canned soups, processed games and energy drinks over four weeks. The youth replaced JF for nuts, seasonal fruits and vegetables. Almost all participants preferred to exercise in their bedroom or in the hallway of their home for 30 minutes to 1 hour. Tpc had the highest incidence of obesity (61.73%), but when they changed their habits it dropped to 40.29%. The COVID-19 pandemic modified the diet and body weight in young people in Nayarit.